Myth-making and History: The Visual Transformation of Boadicea in Eighteenth-Century History Books - Isabelle Baudino (XVII-XVIII)
Boadicea’s absence from British visual culture was conspicuous until the mid-eighteenth century. This essay explores the evolution of Boadicea’s portrayal in book illustrations and in the visual arts, focusing on her transformation from a tragic queen to a classical heroine. Initially depicted as a theatrical character, Boadicea was given a prominent role in British antiquity as a model of resilience and bravery. The reinterpretation of her character owed much to the development of neoclassical aesthetics. Artists like John Opie, Thomas Stothard or Robert Smirke reimagined Boadicea draped in classical garb, thus ennobling her character. Moreover, Boadicea’s portrayal as an eloquent orator aligned with the classicizing of her appearance, contributing to her symbolic status as defender of British liberty. While originally depicted as a barbarian, Boadicea ultimately became emblematic of imperial ideology, an allegory of Britain’s civilizing mission and a protector of British institutions, exemplifying how historical figures can be reinterpreted and demonstrating the essential part played by visual culture in such shifts.